Imagining Air Cultural Axiology and the Politics of Invisibility - Konrad, Tatiana (University of Exeter Press, 2023)
This book tackles air as a cultural, medical, and environmental phenomenon. Its major aim is to explore air's visibility and invisibility within the environment through the investigation of such phenomena as pollution and pandemics. The book provides environmental and medical perspectives on air, in particular how it has historically been envisioned in U.S., Canadian, and British cultural and literary narratives, and explores how these representations and the constructed meanings of air can help us understand the complex nature of air as it pertains to the COVID-19 pandemic, air pollution, and broader environmental degradation.